Øjne - Sander Haj-Mohamed, Monia (Peripeti, 2022)
Eyes (excerpt from the manuscript) Eyes was a theatre performance at Momentum Theatre in Odense that took place from September 25th– October 16th , 2021. In Eyes the audience enters a tiered seating with a script on every second chair. The stage is empty. When seated the spectators negotiate who reads what lines from this script about how the state exerts its power through our bodies.